Environmental resilience: perspectives, strategies and applications - Othman, Rashidi; Mat Ali, Qurratu Aini; Johari, Nursyafica Nadia; Mohd Hatta, Farah Ayuni (Nova Science Publishers, Inc., 2024)
Over the past forty years, several disciplines have adopted and used the term “resilience” to describe the ecological, psychological, sociological, organisational, socio-technical, and social-ecological systems. Environmental resilience, noted during natural hazards, was initially recognised as the primary basis for assessing the hazards’ effects. A community’s resilience is described as “its ability to recover using its resources” in an environment where many countries have experienced varied degrees of natural and man-made hazards. The topography, weather patterns, location, prevailing climate, hydro climatology, and application of management strategies within the region are a few parameters that impact the degree of severity of a hazard by minimising, adapting, and sustaining it. Many variables, including natural and manmade hazards, can affect most countries across the globe. Lacklustre management strategies make impoverished communities even more vulnerable to external factors such as climate change. The key factors that influence vulnerability and resilience to environmental hazards include ethnicity, social class, age, sexual orientation, and nationality. Hence, communities must enhance ecological resilience (ER) to decrease, adapt, and eliminate the occurring damages